Pollinators and floral visitors of two orchids in a protected natural area in Tuxpan, Veracruz - Alanís Méndez, José Luis; Ortiz Santos, Luz del Carmen; Chamorro Florescano, Ivette Alicia; Pech Canché, Juan Manuel; Limón, Francisco (Ecosistemas y Recursos Agropecuarios, 2019)
Floral visitors, particularly pollinators, are important during the life cycle of many orchids. However, despite their biological importance, this information is still unknown in many species, particularly those in mangrove forests. The aim of this research was to study the floral visitors, as well as the pollinators, of the two orchid species Myrmecophila grandifloraand Brassavola nodosa, in a protected natural area with mangrove (RAMSAR), in Tuxpan, Veracruz, Mexico. Ants of different genera were the floral visitors of M. grandiflora, its pollinator is the carpenter bee, Xylocopa nautlana. In B. nodosa, were observed mosquitoes and ladybugs as floral visitors, the pollinator could not be registered, but it is possible that it is a species of moth (Scopula sp.). Finally, this study provides field information about floral visitors and pollinators in two orchid species in mangrove ecosystems and the evidence for pollination.